2017
DOI: 10.1149/07801.3189ecst
|View full text |Cite
|
Sign up to set email alerts
|

Important Roles of Ceria-Based Materials on Durability of Hydrogen and Oxygen Electrodes for Reversible SOEC/SOFC

Abstract: We have examined the durability of oxygen and hydrogen electrodes for reversible solid oxide cells (R-SOCs). The use of a dense, uniform samaria-doped ceria (SDC) interlayer was very important to obtain high performance and high durability of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) -SDC composite oxygen electrode. Double-layer hydrogen electrodes, consisting of SDC scaffold with highly dispersed Ni-Co nanoparticles as the catalyst layer (CL) and a thin current collecting layer (CCL) of either Ni-SDC or Ni-YSZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The industrial partners in AD ASTRA (SOLIDPower and Sunfire) have among the most extensive records of SOC operation in the field, and world-class expertise on SOC manufacturing. This precious demonstration record and know-how -in both SOFC and SOEC operation -has led to the identification of three critical components limiting SOC stack lifetime: Development Program (ALCA) from Japan Science and Technology Agency (JST) [3][4][5] Harnessing degradation: approach and methodology in AD ASTRA…”
Section: International Collaborationmentioning
confidence: 99%
“…The industrial partners in AD ASTRA (SOLIDPower and Sunfire) have among the most extensive records of SOC operation in the field, and world-class expertise on SOC manufacturing. This precious demonstration record and know-how -in both SOFC and SOEC operation -has led to the identification of three critical components limiting SOC stack lifetime: Development Program (ALCA) from Japan Science and Technology Agency (JST) [3][4][5] Harnessing degradation: approach and methodology in AD ASTRA…”
Section: International Collaborationmentioning
confidence: 99%
“…8,13,18,19 We have engaged in the research and development of highperformance electrodes with novel architecture for the R-SOC. 16,17,[20][21][22][23][24][25][26][27][28][29] Very recently, we found that the durability of a double-layer H 2 (DL) electrode, consisting of a SDC scaffold [samaria-doped ceria (CeO 2 ) 0.8 (SmO 1.5 ) 0.2 ] with highly dispersed Ni 0.9 Co 0.1 nanoparticles as the catalyst layer (CL) and a thin current-collecting layer (CCL) of Ni-YSZ cermet, was greatly improved via reversible cycling operation between the SOEC and SOFC-modes. 28 In the present work, we focus on the stabilization mechanism of the microstructure of the CL in our H 2 electrode via reversible cycling operation.…”
mentioning
confidence: 99%
“…28 In the present work, we focus on the stabilization mechanism of the microstructure of the CL in our H 2 electrode via reversible cycling operation. The button cell was prepared in the manner similar to that described previously, [24][25][26] but we will briefly outline the protocol here.…”
mentioning
confidence: 99%
“…3,4 We have engaged in the research and development of electrodes for the R-SOC with novel architecture. [5][6][7][8][9][10][11][12][13][14][15] The oxygen electrode, consisting of a composite of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ (LSCF) and (CeO 2 ) 0.8 (SmO 1.5 ) 0.2 (SDC) with SDC interlayer, in which the SDC acted as a highly effective oxide ionic conductor in oxygen atmosphere, exhibited quite reversible and durable performance for both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). 8,12,13 The use of a dense and uniform SDC interlayer was essential to obtain high durability (suppression of the diffusion of Sr and Zr components), while maintaining high performance, in an accelerated stress test at 900 °C for 5500 h. [12][13][14] Mixed ionic and electronic conduction of SDC in a reducing atmosphere plays an important role in the operation of the hydrogen electrodes.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] The oxygen electrode, consisting of a composite of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ (LSCF) and (CeO 2 ) 0.8 (SmO 1.5 ) 0.2 (SDC) with SDC interlayer, in which the SDC acted as a highly effective oxide ionic conductor in oxygen atmosphere, exhibited quite reversible and durable performance for both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). 8,12,13 The use of a dense and uniform SDC interlayer was essential to obtain high durability (suppression of the diffusion of Sr and Zr components), while maintaining high performance, in an accelerated stress test at 900 °C for 5500 h. [12][13][14] Mixed ionic and electronic conduction of SDC in a reducing atmosphere plays an important role in the operation of the hydrogen electrodes. A double-layer (DL) hydrogen electrode, consisting of an SDC scaffold with highly dispersed Ni-Co nanoparticles as the catalyst layer (CL) and, on top of it, a thin Ni-SDC or Ni-YSZ cermet as the current collecting layer (CCL), exhibited highly reversible performance at 750 °C and 800 °C via control of the microstructure.…”
mentioning
confidence: 99%